Metalocalypse. Army of the doomstar [videorecording (Blu-Ray)] (Warner Bros., 2023)
After the heroic rescue of Toki Wartooth, DETHKLOK frontman Nathan Explosion finds himself traumatized in a BRUTAL professional and romantic flat-spin all while he is tasked with fulfilling the prophecy and confronting the ultimate songwriting challenge: write the SONG OF SALVATION and save the planet. Can Nathan Explosion look beyond his brutally damaged ego to save his band, stop the Metalocalypse, and finally face the ultimate evil: Salacia?